Effect Of Ball Clay Addition In Slip Casting In Making Of Gloves Former - Zulkifli, Farzana (Universiti Sains Malaysia, 2022)
One atom thick, two-dimensional carbon materials graphene have unique properties which includes ultrahigh carrier mobility, large surface area and others. Due to its unique properties, it become a rising star in the field of technological application such as supercapacitors, batteries, flexible and transparent conductors, fuel cells, solar cells, hydrogen storage, electrochemical sensors, and others. The objective of this work is to investigate the optimum voltage of electrochemical exfoliation to synthesis the best quality of reduced graphene oxide (rGO) from spent battery. An introduction to graphene and its derivatives and the concept of electrochemical exfoliation synthesis method has been discussed in this work. Further examination on physical properties such as structure, phase, chemical species, morphologies and its electrochemical properties characterized by using cyclic voltammetry (CV) and galvanostatic charge- discharge (GCD) have been described and presented. Electrochemical exfoliations were carried out at various voltage which are 4.0, 4.5, 5.0, 5.5 and 6.0 V. 4.5 V sample was selected to performed reduction treatment for further electrochemical properties characterization. The structural analysis confirmed that the existence of graphite and graphene oxide. The morphology and elemental analysis confirmed that loose, flexible and freely oriented graphene sheet layers existed and presence of oxygen containing functional group. Electrochemical characterization was performed for 4.5 V sample after reduction treatment. In cyclic voltammetry (CV), the rGO have the best performance at the optimum scan rate (10 mV s-1) where its specific capacitance is 80.40 Fg-1. In galvanostatic charge-discharge (GCD), increase in current densities results in lowest specific capacitance.